Isolasi dan Identifikasi Bakteri Termofilik dari Sumber Air Panas di Moso Distrik Muara Tami Kota Jayapura Provinsi Papua - Dirk Y.P. Runtuboi; Tri Gunaedi; Maria Simonapendi; Nadya N.L. Pakpahan (Jurnal Biologi Papua, 2018)
Thermophilic bacteria are bacteria that are able to survive in environmental conditions with high temperatures. Thermophilic bacteria are one of the important sources of thermostable enzymes that can be isolated from geothermal environments such as hot springs with temperatures ranging from 50–80 oC. Aims of the study to isolate and identify local isolates of thermophilic bacteria from hot springs in Moso Muara Tami District, Papua. The results showed that 7 isolates (A1, A2, A3, A4, B1, B2, and B3) that were isolated and identified based on phenotypic characters were included in the genus Bacillus.  Key words: Thermophilic, characterization, isolation, identification, phenotypic.